Correction: Clinical applications of infrared and Raman spectroscopy: state of play and future challenges. Issue 8 (29th March 2018) - Baker, Matthew J.; Byrne, Hugh J.; Chalmers, John; Gardner, Peter; Goodacre, Royston; Henderson, Alex; Kazarian, Sergei G.; Martin, Francis L.; Moger, Julian; Stone, Nick; Sulé-Suso, Josep
Abstract : Correction for 'Clinical applications of infrared and Raman spectroscopy: state of play and future challenges' by Matthew J. Baker, et al., Analyst, 2018, DOI: 10.1039/c7an01871a.